Guidelines for sustained growth in the EU? The concept and consequences of the Broad Economic Policy Guidelines - Eckhard Hein; Torsten Niechoj (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2005)
The Broad Economic Policy Guidelines contain the answers of the European Commission and the governments of the EU-member countries to the European growth and employment problems. These guidelines have been the major EU-economic policy concept for around ten years now. They can be seen as a synthesis of the economic policy regime dominating the EU since the early to mid 1990s. However, this concept has not been able to generate sustained growth and low unemployment in the EU as a whole. Examining the guidelines we show the weaknesses of the underlying economic policy model and outline an alternative concept which promises more growth and employment for Europe in the long run.
urn:nbn:de:101:1-2008081458
Keywords: E61; E62; E63; E64; 330; Broad economic policy guidelines; European Union; monetary policy; wage policy; fiscal policy; policy co-ordination